The Savvy Survey #8: Pilot Testing and Pretesting Questionnaires - Anil Kumar Chaudhary; Glenn D Israel (EDIS)
It is a good practice to pre-test a questionnaire after the initial design and formatting are completed. Based on studies conducted by researchers, pre-testing can be implemented using various methods. A number of possible pre-testing methods are described in this 6-page fact sheet was written by Anil Kumar Chaudhary and Glenn D. Israel, and published by the UF Department of Agricultural Education and Communication, December 2014.